2011
DOI: 10.1017/jfm.2011.165
|View full text |Cite
|
Sign up to set email alerts
|

Exact tensor closures for the three-dimensional Jeffery's equation

Abstract: This paper presents an exact formula for calculating the fourth-moment tensor from the second-moment tensor for the three-dimensional Jeffery's equation. Although this approach falls within the category of a moment tensor closure, it does not rely upon an approximation, either analytic or curve fit, of the fourth-moment tensor as do previous closures. This closure is orthotropic in the sense of Cintra & Tucker (J.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 23 publications
1
91
0
Order By: Relevance
“…This necessitates the need for a closure by which the higher order orientation tensor is approximated as a function of a lower order tensor, i.e., A = f (A). There exist many closure approximations in the literature of A in terms of A (see e.g., [13,14,28,[40][41][42][43][44][45][46]] to list just a few) and several for the sixth-order orientation tensor (see e.g., [30,47,48]). Montgomery-Smith et al [45] demonstrated that the orthotropic fitted (ORT) closure implemented by VerWeyst and Tucker [28] and the fast exact closure (FEC) [45] are the most accurate.…”
Section: Fiber Orientation Modelingmentioning
confidence: 99%
“…This necessitates the need for a closure by which the higher order orientation tensor is approximated as a function of a lower order tensor, i.e., A = f (A). There exist many closure approximations in the literature of A in terms of A (see e.g., [13,14,28,[40][41][42][43][44][45][46]] to list just a few) and several for the sixth-order orientation tensor (see e.g., [30,47,48]). Montgomery-Smith et al [45] demonstrated that the orthotropic fitted (ORT) closure implemented by VerWeyst and Tucker [28] and the fast exact closure (FEC) [45] are the most accurate.…”
Section: Fiber Orientation Modelingmentioning
confidence: 99%
“…This exact closure is stated explicitly in [14] for the scenario when the suspension is dilute. For the sake of labeling, the present closure retains the reference Exact Closure, as it is exact for Jeffery's equation without diffusion terms.…”
Section: The Fast Exact Closurementioning
confidence: 99%
“…(6), where A is computed from A using Eqs. (38) and (39) as derived in [14]. This approach only gives the exact answer to Eqs.…”
Section: The Fast Exact Closurementioning
confidence: 99%
See 1 more Smart Citation
“…More sophisticated closures have been employed in the literature (see, e.g., Ref. [18] and references therein); here we focus on the simplest model of rodlike-polymer solution that may display instabilities at low Reynolds number. In addition, we disregard Brownian rotations assuming that the orientation of polymers is mainly determined by the velocity gradients.…”
mentioning
confidence: 99%